Hospitalisation costs of metastatic melanoma in France; the MELISSA study (MELanoma In hoSpital coSts Assessment) - Jérôme Fernandes; Bruno Bregman; Patrick Combemale; Camille Amaz; Lucie de Léotoing; Alexandre Vainchtock; Anne-Françoise Gaudin (BMC, 2017)
Abstract Background Management of metastatic melanoma is changing rapidly following the introduction of innovative effective therapies, with consequences for the allocation of healthcare resources. The objective of this study was to assess hospitalisation costs of metastatic melanoma in France from 2011 to 2013 from the perspective of the government payer. Methods The population studied corresponded to all adults with metastatic melanoma hospitalised in France between 1st January 2011 and 31st December 2013 who required chemotherapy, immunotherapy or radiotherapy due to tumour progression and unresectable Stage III or Stage IV melanoma. Metastatic melanoma was identified by ICD-10 codes documented in the hospital patient discharge records. For each patient, hospital stays were stratified into a pre- or post- progression health state using proxy variables for the RECIST criteria. All healthcare expenditure documented in the French national hospital claims system database and incurred between the index hospitalisation (or change of progression state) and the end of follow-up were analysed. For the principal analysis, valuation of healthcare resource consumption was performed using official national hospitalisation tariffs. Any expensive therapy administered during the stay was documented from a linked database of expensive drugs (FICHCOMP). Results Seventy-eight thousand seven hundred fifty hospital stays by 10,337 patients with metastatic melanoma were identified over the three-year study period. Annual per capita costs of hospitalisation were € 5046 in the pre-progression stage and € 19,006 in the post-progression stage. Hospitalisations attributed to adverse drug reactions to chemotherapy or immunotherapy were observed in 27% of patients. Annual per capita costs of these hospitalisations related to adverse drug reactions were € 3762 in the pre-progression stage and € 5523 in the post-progression stage. Conclusions Hospitalisation costs related to metastatic melanoma rise substantially as the disease progresses. Treatment strategies which slow down disease progression would be expected to reduce costs of hospitalisation for metastatic melanoma, although they may also entail significant acquisition costs. This will entail organisational changes of resource allocation for the treatment of metastatic melanoma in hospitals.